New species of Ornebius (Orthoptera: Mogoplistidae; Mogoplistinae) from Siargao Island of the Philippines - Tan, Ming Kai; Ingrisch, Sigfrid; Baroga-Barbecho, Jessica B.; Yap, Sheryl A. (Zootaxa, 2019)
Two new species of Ornebius are described from Siargao Island, Mindanao of the Philippines: O. alvarezi sp. nov. and O. bioculatus sp. nov. These sympatric scaly crickets have diverging genitalia morphology, with O. alvarezi sp. nov. resembling congeners from Borneo whereas O. bioculatus sp. nov. resembling congeners from Sulawesi. With the new findings, the number of Ornebius species known from the Philippines increases to four.